Performing the Holy Spirit: Ritualised Manifestation of Faith in an African Independent Church - Skelton, C. (Journal for the study of religion, 2010)
This research examines the aesthetic manifestations of religious belief, particularly in the Holy Spirit, through consideration of the performative dimensions and ritualised behaviours in the church services of an African Independent Church, namely, the New Gospel Church in Zion of Africa (NGCZA). The significance of specific objects and activities within the sacred context and how these contribute to the performance of belief among the congregants is central to this consideration. Drawing on the ritual performance theories of Turner and Schechner, the article argues that NGCZA church activity is highly influenced by a belief in the Holy Spirit. The results also indicated that religious activity enables an environment that is conducive to the emergence of liminal identities. Enabled from within a ritual frame that guides proceedings, the use of religious objects such as uniforms, clothing and drums facilitate an invocation of the Holy Spirit for the purposes of healing. Religious belief, once enacted, results in highly performative activities and actions within spiritually charged spaces.The Holy Spirit gives people the mystical and second sense to see things, which is believed to come from the Christian God, and which in former times would have been a sign of possession by ancestral spirits alone; it is also the ultimate authority in divination, and the remedy for spiritual and physical sickness. (Armitage, cited by Anderson 1991: 38)We will know one another better by entering one another’s performances and learning their grammars and vocabularies. (Turner 1990: 1)